Tematika materinjenja v izbranih dramskih delih Simone Semenič - Brataševec, Laura (Jezik in slovstvo, 2015)
Playwright, dramaturge and producer Simona Semenič has enriched Slovenian drama with many drama pieces conveying a new, different view of existing topics. Of a particular interest is a depiction of motherhood that moves away from the dominant presentations of the mother, as well as descriptions of motherhood-related motifs. This distinguishes Semenič from other male and female playwrights. The critical and emotional approach pervading all of her texts has led her to produce numerous remarkable works that have seen several performances.
Keywords: Semenič, Simona; drama; dramatika; materinstvo; materinjenje; ženski liki